2017
DOI: 10.1103/physrevapplied.8.024001
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar and Bipolar High-Magnetic-Field Sensors Based on Surface Acoustic Wave Resonators

Abstract: While surface acoustic wave (SAW) sensors have been used to measure temperature, pressure, strains, and low magnetic fields, the capability to measure bipolar fields and high fields is lacking. In this paper, we report magnetic surface acoustic wave sensors that consist of interdigital transducers made of a single magnetostrictive material, either Ni or TbFe 2 , or based on exchange-biased (Co=IrMn) multilayers. By controlling the ferromagnet magnetic properties, high-field sensors can be obtained with unipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…parallel to the easy axis of the full film (sample VIDT//EA) and the VSM test repeated. As expected from a previous study [27] and micromagnetism theory, the easy axis of magnetization remains along X+90°.…”
Section: Magnetometrysupporting
confidence: 87%
“…parallel to the easy axis of the full film (sample VIDT//EA) and the VSM test repeated. As expected from a previous study [27] and micromagnetism theory, the easy axis of magnetization remains along X+90°.…”
Section: Magnetometrysupporting
confidence: 87%
“…From the phase change the magnetic-field strength can be calculated. Besides other SAW sensors [ 5 , 6 , 7 , 16 , 17 , 18 ], the delta-E effect is used for magnetic-field sensing with magnetoelectric composite resonators operating in bending or bulk modes [ 19 , 20 , 21 , 22 ]. In contrast to such sensors, the sensitivity of Love-wave magnetic-field sensors is expected to benefit from shear-resonance, as the elastic modulus change of the magnetostrictive material was reported to be largest for shear stress [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rather promising recent experiments [29][30][31][32] have demonstrated that the propagation of SAWs in piezoelectric substrates can be controlled by a thin magnetic layer placed atop the substrate. The use of such heterostructures allows one to combine in a single device a highquality piezoelectric substrate (like LiNbO 3 ) and a ferromagnet with large magnetostriction (e.g., Ni).…”
Section: Introductionmentioning
confidence: 99%